JURNAL ILMU KEHUTANAN : development of Drying Schedule of Superior and Conventional Teak Wood of Ten Years-Old Planted in Blora, Central Java - Tomy Listyanto , Yusuf Setia Darmawan (Fakultas Kehutanan UGM, 2016)
The aims of this study were to investigate drying defect characteristics, to develop proper drying schedule, and to analyze the relationship between the developed drying schedule and its wood properties.